Quantum-enhanced sensing using non-classical spin states of a highly magnetic atom. Issue 1 (December 2018) - Chalopin, Thomas; Bouazza, Chayma; Evrard, Alexandre; Makhalov, Vasiliy; Dreon, Davide; Dalibard, Jean; Sidorenkov, Leonid; Nascimbene, Sylvain
Abstract Coherent superposition states of a mesoscopic quantum object play a major role in our understanding of the quantum to classical boundary, as well as in quantum-enhanced metrology and computing. However, their practical realization and manipulation remains challenging, requiring a high degree of control of the system and its coupling to the environment. Here, we use dysprosium atoms—the most magnetic element in its ground state—to realize coherent superpositions between electronic spin states of opposite orientation, with a mesoscopic spin sizeJ = 8. We drive coherent spin states to quantum superpositions using non-linear light-spin interactions, observing a series of collapses and revivals of quantum coherence. These states feature highly non-classical behavior, with a sensitivity to magnetic fields enhanced by a factor 13.9(1.1) compared to coherent spin states—close to the Heisenberg limit 2J = 16—and an intrinsic fragility to environmental noise. Moderate-size coherent superpositions of spin states allow quantum enhancements in metrology. Here, the authors exploit the large electronic spin of dysprosium atoms to realize mesoscopic spin superpositions, allowing a 14-fold quantum enhancement in magnetic field sensitivity, close to the Heisenberg limit.